2014
DOI: 10.1021/ja410684q
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal Preparation of an Electrocatalytic Metalloporphyrin MOF Thin Film and its Redox Hopping Charge-Transfer Mechanism

Abstract: A thin film of a metalloporphyrin metal-organic framework consisting of [5,10,15,20-(4-carboxyphenyl)porphyrin]Co(III) (CoTCPP) struts bound by linear trinuclear Co(II)-carboxylate clusters has been prepared solvothermally on conductive fluorine-doped tin oxide substrates. Characterization of this mesoporous thin film material, designated as CoPIZA/FTO, which is equipped with large cavities and access to metal active sites, reveals an electrochemically active material. Cyclic voltammetry displays a reversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
291
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(304 citation statements)
references
References 80 publications
8
291
0
2
Order By: Relevance
“…While an understanding of the mechanisms of charge transport in MOFs is in its infancy, it is generally believed that charge hopping between components predominates for semiconducting MOFs, including mixed-valence frameworks such as Prussian blue, 11 , 12 and can explain electron transfer in MOF fi lms during electrochemical experiments. 13 The variable-range hopping model, postulated by Mott 14 and originally developed for highly disordered systems with localized charge carriers, describes low-temperature conductivity ( σ ) in semiconductor solids with localized chargecarrier states, where conduction in three-dimensional systems follows a temperature ( T ) dependence of log σ ∼ T -1/4 . This model has had mixed success in the interpretation of MOF…”
Section: General Design Considerationsmentioning
confidence: 99%
“…While an understanding of the mechanisms of charge transport in MOFs is in its infancy, it is generally believed that charge hopping between components predominates for semiconducting MOFs, including mixed-valence frameworks such as Prussian blue, 11 , 12 and can explain electron transfer in MOF fi lms during electrochemical experiments. 13 The variable-range hopping model, postulated by Mott 14 and originally developed for highly disordered systems with localized charge carriers, describes low-temperature conductivity ( σ ) in semiconductor solids with localized chargecarrier states, where conduction in three-dimensional systems follows a temperature ( T ) dependence of log σ ∼ T -1/4 . This model has had mixed success in the interpretation of MOF…”
Section: General Design Considerationsmentioning
confidence: 99%
“…Thus, MOFs exhibit poor charge transport properties that may be described as diffusive motion of localized charge carriers. [29][30][31] In recent years, different design strategies have been adopted to construct conducting MOFs, for example, using pi-stacking in aromatic linkers, 30,32,33 the formation of 1-D chains of alternating metal-sulfur or metal-oxygen atoms, 34,35 and infiltration with guest molecules or nanocrystals. 36,37 In these MOFs, the porosity (needed for motion of ions) and chemical stability (needed during catalysis) are compromised.…”
mentioning
confidence: 99%
“…119 Using a solvothermal preparation, Ahrenholtz et al prepared electrocatalytic metalloporphyrin MOF thin films on fluorine-doped tin oxide transparent electrodes and analyzed the redox hopping character of the films. 118 The work shows that the porous nature of the film responds to efficiently reduce CCl 4 and demonstrates the potential use of these types of structures for electrocatalysis. A limiting factor for this system may be the moderate rate of charge transfer through the MOF structure.…”
Section: Porphyrin Polymers As Photocatalystsmentioning
confidence: 84%
“…Also, developing methods to deposit and orient these systems onto electrodes to optimize catalytic ability is important for future integration into photochemically viable systems. 66,118 Jahan et al linked an Fe-TCPP MOF to sheets of graphene by functionalizing graphene oxide with conjugated pyridine ligands. They showed that upon coordination with reduced graphene oxide the crystallinity of the MOF changed to have an increased porosity.…”
Section: Porphyrin Polymers As Photocatalystsmentioning
confidence: 99%